An investigation of the English language demands of mathematical texts on data handling used in intermediate phase mathematics - Jones, Angela Peta (Rhodes University, Faculty of Education, Department of Education)
In the Intermediate Phase the majority of South African learners are transitioning from learning in their mother tongue to learning in English as well as from learning to read to reading to learn, and this is a major challenge. Textbooks are a key mediating artefact in the learning of mathematics and they present a challenge to the learner in terms of the language comprehension demands The data handling sections of mathematics textbooks are particularly dense in text. This is an important part of the mathematics curriculum as it is the beginning of statistical literacy learning. We need to be able to question, evaluate claims based on data, create arguments we can defend and use data meaningfully, it is thus crucial that learners acquire statistical literacy. This research sets out to examine the text in the data handling sections of four Intermediate Phase Mathematics book series in order to answer the following research question: What are the language comprehension demands of English mathematical texts on data handling that are used in South African Intermediate Phase Mathematics? The theories framing the study are Vygotsky's sociocultural theory and Cummins' second language acquisition theory. It is an interpretivist mixed method case study that takes the form of a document analysis.. The findings indicate that many units in the books analysed have a higher readability level than the grade level and will thus present a challenge to learners in terms of their ability to access the mathematical content. An analysis of the linguistic complexity revealed that the features contributing most to the complexity of the texts included words with seven or more letters, prepositional phrases, infinitives, complex verbs and complex/compound sentences. An examination of the non-textual elements revealed that most of them are accurate, connected, concise, contextual and these add to the comprehensibility although there were a few which could be possibly be distractors. It is hoped that the empirical findings of this study, will sensitise educators and publishers involved with the design of textbooks and workbooks to the type of language currently found and that they might give attention to the needs of English language learners when developing these texts.
Keywords: Mathematics-- Study and teaching (Elementary) -- South Africa; Middle school education -- South Africa; Information storage and retrieval systems Mathematics; Language complexity; Textbooks Readability; Language arts Correlation with content subjects -- South Africa; Content area reading -- South Africa